The Suprasegmental Analysis On Jokowi’s Speech Of “Lonjakan Kasus Covid-19 dan Penerapan PPKMMikro On 23rd Of June 2021” - Lela Rahmawati; Hilda Hastuti; Sutarman Sutarman; Alan Cahya Saputra (Jurnal Ilmiah Telaah, 2022)
Abstract:This study aims at describing learners’ features of pronunciation in terms of the suprasegmental aspects found in Jokowi’s Specch of Lonjakan kasus Covid-19 dan penerapan PPKM Mikro on 23rdof June 2021. Suprasegmental information applies to several different linguistic phenomena such as pitch, duration, and loudness. Speech not only conveys question word or sentence, but also the meaning behind every utterance phonologically. In this research, the using of the supra-segmental aspect in order to reveal the true meaning and contextual meaning of what Jokowi’s delivered in his speech. The result of this study revealed that phone segment in the text of Jokowi’s speech is divided into two categories such as the form of language and the language features in the speech text. The form of language is related to the form of segment which is divided into three sub-categories such as high intonation segment, moderate intonation segment, and low intonation segment.